Impact of delayed care on surgical management of patients with gastric cancer in a low‐resource setting. Issue 8 (31st October 2018) - Martin, Allison N.; Silverstein, Allison; Ssebuufu, Robinson; Lule, Joseph; Mugenzi, Pacifique; Fehr, Alexandra; Mpunga, Tharcisse; Shulman, Lawrence N.; Park, Paul H.; Costas‐Chavarri, Ainhoa
Abstract : Background: Gastric cancer is the fifth most common cancer in Eastern Africa. Diagnostic delays in low‐resource countries result in advanced disease presentation. We describe perioperative management of gastric cancer in Rwanda. Methods: A retrospective review of records at three hospitals was performed to identify gastric adenocarcinoma cases from January 2012 to June 2016. Multiple perioperative and tumor‐related variables were collected. Descriptive and bivariate analyses were performed. Results: The final analysis included 229 patients with gastric cancer. Median age was 58 years (interquartile range [IQR] 49‐65) and 49.6% were female ( n = 114). Patients reported symptoms (ie, weight loss, epigastric pain) for a median time of 12 months (IQR 7.5‐24). On presentation, 18.8% ( n = 43) had gastric outlet obstruction; 13.5% ( n = 31) had a palpable mass. Fifty‐one percent ( n = 117) underwent an operation; of these, 74% ( n = 86) received gastrojejunostomy or were inoperable; and 29% ( n = 34) underwent curative resection. Palliative care referrals were made for 9% ( n = 20). Pathology reports were available for 190 patients (83.0%). Only 11.3% ( n = 26) had Helicobacter pylori ( H. pylori ) testing of which 65.4% tested positive ( n = 17). Conclusions: A majority of patients presented with advanced disease. Very few patients had a curative resection. Significant advances in diagnosis and treatment are needed to improve the care of gastric cancer patients in Rwanda.